2006
DOI: 10.1093/nar/gkl681
|View full text |Cite
|
Sign up to set email alerts
|

Antibody binding loop insertions as diversity elements

Abstract: In the use of non-antibody proteins as affinity reagents, diversity has generally been derived from oligonucleotide-encoded random amino acids. Although specific binders of high-affinity have been selected from such libraries, random oligonucleotides often encode stop codons and amino acid combinations that affect protein folding. Recently it has been shown that specific antibody binding loops grafted into heterologous proteins can confer the specific antibody binding activity to the created chimeric protein. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 77 publications
2
28
0
Order By: Relevance
“…In addition, antibody heavy chain CDR3 sequences have been inserted into several loop regions of superfolder GFP, a GFP variant evolved for high stability and improved folding kinetics (17), to create libraries of single CDR3-inserted GFP. Results from this study indicated that insertion at many sites substantially reduces GFP fluorescence as seen previously with standard GFP variants (18). Three loop regions of the superfolder GFP, however, tolerated single loop CDR insertions (including Asp-173-Gly-174) such that it was possible to isolate fluorescent binders against protein targets using T7 phage display, with the best being a 470 nM lysozyme binder (19).…”
supporting
confidence: 53%
See 1 more Smart Citation
“…In addition, antibody heavy chain CDR3 sequences have been inserted into several loop regions of superfolder GFP, a GFP variant evolved for high stability and improved folding kinetics (17), to create libraries of single CDR3-inserted GFP. Results from this study indicated that insertion at many sites substantially reduces GFP fluorescence as seen previously with standard GFP variants (18). Three loop regions of the superfolder GFP, however, tolerated single loop CDR insertions (including Asp-173-Gly-174) such that it was possible to isolate fluorescent binders against protein targets using T7 phage display, with the best being a 470 nM lysozyme binder (19).…”
supporting
confidence: 53%
“…This approach therefore results in selection of only fluorescent binders, something that could not be guaranteed using phage display without the aid of labor-intensive secondary confirmations (18). Moreover, while there is not a perfect quantitative agreement between surfacedisplayed and secreted GFAb stability, fluorescence and binding properties (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The heavy chain variable region, and in particular, the heavy chain CDR3, are considered to be the most important determinants of recognition [17,18,55], exemplified by experiments in which HCDR3 sequences from an anti-lysozyme VHH antibody (VHH) [56] were transplanted into neocarzinostatin [57] and sfGFP [58], conferring lysozyme binding activity. HCDR3’s have even been harvested as diversity elements [59,60] and binders have been selected from libraries in which they provided the only diversity [18,58]. As a result, deep sequencing initially concentrated on HCDR3, expanding to VH as read lengths increased.…”
Section: Applicationsmentioning
confidence: 99%
“…28 Furthermore, an antigen-binding CDR loop was transferred into a structurally equivalent surface binding loop of nonantibody proteins while maintaining the original function of the acceptor protein, resulting in bifunctional molecules. 29,30 In this study, the highaffinity target-binding L56 (the DR4-binding L56 of KD413 and the DR5/DR4-binding L56 of KD548), which was identified by loop mapping, was grafted onto the structurally compatible L34 of wild-type PgnKD2, generating monovalent KD variants with target binding specificity and affinity (i.e., mKD413-4 and mKD548-5) (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%